2013
DOI: 10.1115/1.4025742
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Method to Measure the Cutting Temperature in Process by Using an Internally Cooled Smart Cutting Tool

Abstract: This paper presents a novel approach to measure the cutting temperature in process and control it to some extent by using an internally cooled smart cutting tool with a closed internal cooling circuitiy. Numerical modeling based on the finite element analysiscomputational fluid dynamics (CFD) method is carried out by using ANSYS and FLUENT, then the suiface temperature distribution of the tool is fitted and the equivalent heat transfer coefficient of the tool surface contacting with cooling fluid is computed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Besides the chip-breaker, the macro surface structures shown another function in the previous research. Shu et al [13] manufactured inlet and outlet channels within the tool holder, and then assembled the insert upside down on the tool holder. The channels and grooved chip-breaker made up a sealed flow channel, which functioned as an internal cooling system.…”
Section: Functionsmentioning
confidence: 99%
“…Besides the chip-breaker, the macro surface structures shown another function in the previous research. Shu et al [13] manufactured inlet and outlet channels within the tool holder, and then assembled the insert upside down on the tool holder. The channels and grooved chip-breaker made up a sealed flow channel, which functioned as an internal cooling system.…”
Section: Functionsmentioning
confidence: 99%
“…Previous research showed that the maximum cutting temperature is located at a position that is near the center of the tool-chip contact area. For simplicity, the tool-chip contact face was assumed as a uniform temperature distribution area [14]. There are three different coordinate systems, which are defined as S(XOY), S 1 (…”
Section: Energy Balancingmentioning
confidence: 99%
“…Werschmoeller et al [14] presented a novel approach for obtaining thermal data from hard turning by insertembedded thin film sensors. Shu et al [15] put forward a novel approach to measure and control cutting temperature in process through experimental and numerical modeling method.…”
Section: Introductionmentioning
confidence: 99%